INTEGRATED LIBRARY SERVICE APPLICATION PLATFORM BASED ON THE SMART BOOK SHELF - Teng, Yen Wu; Kun, Chieh Yeh; Ruey, Shun Chen; Chen, Y.C.; Chen, C.C. (Malaysian Journal of Library and Information Science, 2017)
With the advent of the knowledge economy and the prevailing of the information technology,libraries are gradually introducing the automation mechanism to provide more convenient service. The time lag of the information retrieval still has influence on librarians’ and readers’ knowledge of the actual status of the library collections. The current practice is that the circulation record and circulation status are updated at the time when the book is borrowed or returned, with the identification component on the book or media being sensed. However, some readers use the reference books, periodicals and audio-video media in the library, therefore before the books are registered on the counter, the status of books in the library cannot be precisely confirmed, often making the information of the book shelves presented by the library database information not precisely reflecting their actual status. The "Integrated Library Service Application Platform" in this paper employs the RFID (Radio Frequency Identification) technology to construct the smart book shelf, and it is used as the trigger point for updating the retrieval status of the book to eliminate bottleneck at the counter that cannot render the real-time circulation status of book in the library upon borrowing or returning the book. With the help of software agent system to integrate the information architecture of the library and provide intelligent service applications, the overall structure is conducive in enhancing